Expert System Based on Fuzzy Logic: Application on Faults Detection and Diagnosis of DFIG - Ahmed Cheriet; Abdelkader Bekri; Abdeldjebar Hazzab; Hicham Gouabi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Electrical energy production based on wind power is gaining area as renewable resources in the recent years because it gets clean energy with minimum cost. The major challenge for wind turbines is the electrical and the mechanical failures which can occur at any time causing damages and therefore it leads to machine downtimes and to energy production loss. To avoid this problem, several methods have been developed and used. In this paper, we proposed an expert system based on fuzzy logic which can detect and diagnosis DFIG’s faults via the Stator current’s signatures. The fuzzy inference system exploits the root mean square values of the stator’s currents according to expert’s rules to diagnosis the DFIG’s state. The smart proposed expert system is verified using simulations done under Matlab/Simulink. The obtained results are very interesting and show the efficiency of the proposed strategy.